Environmental and spatial planning with ngā Atua kaitiaki: A mātauranga Māori framework. (28th July 2021) - Walker, Dean P.; Ataria, James M.; Hughey, Kenneth F. D.; Park, Patrick T.; Katene, John P.
Abstract: Internationally, Eurocentric hegemonies rooted in coloniality dominate the discourse on environmental wellbeing and sustainable development. Māori frameworks are being used and developed in Aotearoa New Zealand to support bicultural approaches to the management of natural resources and built environments. This paper reports on an Atua (Māori gods and spirits) framework that was found to be valuable as a cultural lens for the co‐creation of a toolkit for assessing the wellbeing of indigenous forests. This article provides guidance on the development and application of kaupapa Māori frameworks, particularly Atua frameworks, in wider geographical contexts including urban design and spatial planning.